125 Evaluation of Antioxidant-Containing Kibble on Serum Antioxidant Biomarkers in Adult Beagles. (21st September 2022) - Panasevich, Matthew; Daristotle, Leighann; Lin, Ching-Yen; Frantz, Nolan
Abstract: The objective of this study was to evaluate oxidative health biomarkers in healthy male and female adult Beagles (n=30, 13 male and 17 female; avg age and BW + SD 4.46 ± 1.41 years; 9.83 ± 2.37 kg) fed a commercial adult maintenance diet (Blue Buffalo Life Protection Formula Adult Chicken and Brown Rice) without (control diet) and supplemented with an antioxidant-containing kibble (test diet; a proprietary blend containing blueberries, cranberries, and other antioxidant-containing ingredients). Both diet offerings analyzed as 25.6% crude protein, 14.4% crude fat, 2.6% crude fiber, 8.6% moisture, 42.6% carbohydrate as-is. We hypothesized that test diet feeding would reduce serum pro-oxidative biomarkers, compared with control diet feeding. The study protocol was first approved by the Institutional Animal Care and Use Committee. All dogs were fed a base kennel maintenance diet (no added antioxidants beyond maintenance requirements) for 14d before treatment phase. Animals were then randomized to control or test for a 28-d treatment period in a randomized cross-over design. Base kennel maintenance diet was provided for a 14d washout, followed by another treatment period. Serum was collected on days 0, 14, and 28 of each treatment period for biomarker analysis. Data were analyzed as a mixed models 2-way ANCOVA (SAS v9.4). Significant differences between treatments were set at P<0.05 and a trend at P<0.10. Average daily food intake and body weight were similar between treatments for the entire study. Serum advanced glycation end-products and malondialdehyde tended (P<0.10) to be reduced when animals were fed test diet compared with control diet. No differences were observed in other antioxidant biomarkers. These data suggest that addition of an antioxidant-containing kibble extruded to preserve antioxidant activity to a maintenance diet results in some favorable modulation of serum antioxidant markers in dogs. The observed trends suggest additional research to elucidate the effects.